Searching for adulthood: young people, citizenship and participation - Martelli, Alessandro; Pitti, Ilaria (SocietàMutamentoPolitica, 2015)
Focusing on the relation between youth and citizenship and between youth and adulthood, the article investigates youth paths of civic and political engagement by presenting the results of a qualitative research conducted in Bologna in 2012 which has involved a sample of young people and a sample of “significant adults” through semi-structured interviews. The intergenerational analysis shows that youth civic and political engagement, still influenced by social and economic factors, can be interpreted as a multiform expression of agency towards an environment perceived as not welcoming for the younger generations.